Impaired Performance on a Cognitively-Based Instrumental Activities of Daily Living Task, the 10-Item Weekly Calendar Planning Activity, in Individuals With Stroke Undergoing Acute Inpatient Rehabilitation - Jaywant, Abhishek; Arora, Catherine; Lussier, Alexis; Toglia, Joan (Frontiers in Neurology, 2021)
Executive dysfunction is common in stroke patients undergoing acute inpatient rehabilitation. However, comprehensive neuropsychological evaluation of executive functions is often not feasible in this setting. Objective, standardized, and performance-based measures of cognitively-based instrumental activities of daily living (C-IADL) can capture everyday executive functions and inform rehabilitation planning and interventions. The goal of this study was to compare performance of individuals with stroke to healthy age-matched adults in performance on the 10-item Weekly Calendar Planning Activity (WCPA). 77 stroke inpatients undergoing rehabilitation and 77 healthy control participants completed the WCPA, a C-IADL measure involving scheduling appointments that requires planning, working memory, shifting, and inhibitory control. Compared to the control group, stroke patients had significantly worse accuracy, made more errors, used fewer cognitive strategies, followed fewer rules, took more time to complete the task, and were less efficient. 83% of stroke patients were less accurate than predicted by their age, and 64% used less strategies than their age prediction. Among 28 participants who screened as having “normal” cognitive function on the Montreal Cognitive Assessment, the majority had deficits on the WCPA. Our results indicate that the WCPA is sensitive to executive dysfunction in stroke patients undergoing acute inpatient rehabilitation and underscores deficits in C-IADL accuracy, efficiency, and strategy use at this stage of stroke recovery. The WCPA may be a useful measure to ascertain executive dysfunction and to incorporate in cognitive rehabilitation.